Optimization Of Extraction Conditions For Total Phenols, Flavonoids, And Antioxidant Activity Of Avocado Seeds (Persea Americana Mill.) Using Simplex Lattice Design - rizqika bastian tomi; Iswandi Iswandi; Opstaria Saptarini (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Avocado pits contain a diverse array of bioactive substances, such as procyanidins, phenolic compounds, triterpenoids, acetogenins, fatty amino acids, and mild acids, all exhibiting antioxidant properties. Antioxidants function by preventing oxidation, reducing the formation of harmful compounds, and protecting against aging, inflammation, and cancer. This research centers on assessing the impact of solvent proportions, pinpointing the ideal solvent mixture, and measuring the overall phenolic and flavonoid levels, along with the antioxidant capacity, of the top-performing solvent applied for extracting compounds from avocado seeds. The research method used the SLD (Simplex Lattice Design) Design Expert method. The extract formula was prepared using sonication, with the results showing 17 formulas for three solvents: acetone, distilled water, and 70% ethanol. Test parameters included phytochemical screening tests, specific and non-specific parameter tests, total phenol tests, total flavonoid tests, and antioxidant activity tests using the DPPH method. Statistical data analysis was performed using Design Expert with ANOVA (Analysis of Variance) output according to the designed experimental design. The results obtained based on the research are the 12th run formula with a solvent ratio of acetone, distilled water, and 70% ethanol (100:0:0) has an extract yield of 3.25%, total flavonoids of 17.302 mgQE/g extract, total phenols of 46.274 mgGAE/g extract, and antioxidant activity of 81.68 ppm, the optimisation results show that the optimum solvent composition is 100% Acetone, without a mixture of 70% Ethanol or Distilled Water.